Recalling a Police Officer from Leave: Problems of Legislation and Practice - О. V. Chornous (Bulletin of Kharkiv National University of Internal Affairs)
The peculiarities of the procedure for recalling police officers from annual leave have been studied. The problems of legal regulation of this institution of labor law have been singled out. It has been noted that the annual leave of a police officer is divided into a basic leave, which may not be less than thirty calendar days, and an additional leave, the duration of which may not exceed fifteen days. It has been noted that the legislator did not provide a mechanism for recalling a police officer from annual leave.